Fiqh Sosial Perspective on Prenuptial Agreements: Harmonizing the Tradition and Modernity in Muslim Communities - Hakim, Muh. Luthfi (Santri: Journal of Pesantren and Fiqh Sosial, 2024)
The acceptance of prenuptial agreements presents contradictory issues among traditional Muslim communities that adhere to conventional Islamic values and modern Muslim communities that seek more comprehensive legal protection. This study aims to analyze these contradictions through the lens of fiqh sosial perspective, relating it to the applicable legal context to provide a thorough understanding of the relevance of these viewpoints in contemporary social and legal practices. Unlike previous research, this study highlights the fiqh sosial approach, positing that this perspective is pertinent in addressing the diverse community attitudes towards prenuptial agreements. The findings indicate that the fiqh sosial approach transcends texts of fiqh by emphasizing contextualization to meet the demands of modern times. In this context, prenuptial agreements can be seen as a way to reinterpret fiqh texts through a formal agreement, specifically through a written prenuptial agreement. Furthermore, prenuptial agreements can serve the public good in marriage practices in Indonesia by developing the kaidah fiqhiyyah “ad-daf'u aqwa min ar-raf'i” through asset protection and preventive measures against potential negative occurrences during the marriage.